Legal Protection for Lessees for Lease Agreements for Buildings on Land with Third Party Ownership (Study of Lease Agreements for Hasaka Villa Canggu) - Ariyanti, Harum; Navisa, Fitria Dewi; Sunardi, Sunardi (International Significance of Notary, 2022)
The implementation of leasing in practice in Bali is leasing which is carried out on land owned by third parties. The problems in this study are related to whether or not PT. Marelti Karya Indonesia entered into a lease agreement for the land and building of Hasaka Villa Canggu which is located on land owned by Ni Luh Kordi. The results of this study indicate that Hasaka Villa Canggu has the right to enter into a rental agreement for a villa building located on private land that is under the control of Ni Luh Kordi to a third party if prior written approval has been obtained from Ni Luh Kordi. which contains that Ni Luh Kordi agrees to give approval to Hasana Villa Cangu to be able to build a building in the form of a villa and in the future lease the villa building to a third party for a certain period of time which is no longer than the lease term of the land. lease agreement made between PT. Marelti Karya Indonesia as the party that leases the Hasaka Villa Canggu which has not yet been built is legal according to the law because it has fulfilled the legal terms of the agreement as stipulated in Article 1320 of the Civil Code. This can happen if prior written approval has been obtained from Ni Luh Kordi which contains that Ni Luh Kordi agrees to give approval to Hasana Villa Cangu to be able to build a building in the form of a villa and in the future lease the villa building to a third party in certain period of time which is no longer than the term of land lease from Hasana Villa Cangu to Ni Luh Kordi. Legal protection can be given to parties who are disadvantaged as a result of defaults on lease agreements on land and buildings. Parties who are harmed by default can ask for money in the nominal amount of the loss caused by default. The next legal protection can be carried out if it turns out that Hasana Villa Cangu has not received written approval from the land owner to be able to lease back Hasana Villa Cangu, then the act committed by Hasana Villa Cangu is classified as an illegal act. Therefore, the agreement made between Hasana Villa Cangu and the lessee does not fulfill the objective legal requirements of the agreement, namely in the form of a halal cause. Therefore, the agreement has legal consequences, namely in the form of null and void, therefore the injured party can ask for compensation from the opposing party in accordance with the nominal loss for the void agreement as explained above. Keywords: Legal Protection; Lease Agreements for Buildings on Land with Third Party Ownership.